8k-(6k+k)=-(2k+6)

Simple and best practice solution for 8k-(6k+k)=-(2k+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8k-(6k+k)=-(2k+6) equation:


Simplifying
8k + -1(6k + k) = -1(2k + 6)

Combine like terms: 6k + k = 7k
8k + -1(7k) = -1(2k + 6)

Remove parenthesis around (7k)
8k + -1 * 7k = -1(2k + 6)

Multiply -1 * 7
8k + -7k = -1(2k + 6)

Combine like terms: 8k + -7k = 1k
1k = -1(2k + 6)

Reorder the terms:
1k = -1(6 + 2k)
1k = (6 * -1 + 2k * -1)
1k = (-6 + -2k)

Solving
1k = -6 + -2k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '2k' to each side of the equation.
1k + 2k = -6 + -2k + 2k

Combine like terms: 1k + 2k = 3k
3k = -6 + -2k + 2k

Combine like terms: -2k + 2k = 0
3k = -6 + 0
3k = -6

Divide each side by '3'.
k = -2

Simplifying
k = -2

See similar equations:

| y=20+6x | | 15p-13p-16= | | 5z-2= | | 4-3x+7=8-5x | | 7x+4=3+4x+22 | | 3X^2-35x=112+7x-4X^2 | | 1-m=6-6-6m | | 2(66)-6= | | 32.73=58.59(W-17.76) | | 4(x-6)=-2(x+3) | | 0-2x+1=0 | | 2w-6=126 | | z-4z=9z-6-z | | (-7+8x)-(x-1)=3x+6 | | 6x-1=2x-21 | | 25.94=5g+3.69 | | z+6=-17 | | 2(3x)+2(x)=320 | | 175-75+48750=50750-150 | | 3x(9-8)+7-11= | | 12z-4z+8=-16 | | 7z-z=-1+3z-1-1 | | 4x+3=6+2x+25 | | 4x^2+4x-5=2x(x+3)-1 | | 1.52g-11=0.40 | | -2-2x=6x-50 | | 0.24p+1.17=1.8 | | 45+90x=585 | | 9x+8y=13.83 | | -5r-5r=4-8r-4r | | 48750-75+175=50750-150 | | 0.24p+1.17=1.29 |

Equations solver categories